Association between Problematic Social Media Use and Academic Procrastination: The Mediating Role of Mindfulness. (3rd July 2022) - Serrano, Danya M.; Williams, Patrick S.; Ezzeddine, Laela; Sapon, Bryan
ABSTRACT: Excessive social media use is a growing concern among educators. However, little research has examined the effects that problematic social media use has on student's academic procrastination and thereby on academic performance. Thus, this study explored the effects of social media use on students' academic procrastination and performance, and the degree to which students' mindfulness mediates these associations. Participants were 233 undergraduate students attending a Hispanic-serving institution. Hierarchical linear regression analyses indicated that problematic social media use significantly predicts academic procrastination. Moreover, the association between problematic social media use and academic procrastination was better explained through mindfulness within academic environments.